2012
DOI: 10.1007/s00401-012-0999-z
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquilin immunoreactivity in cytoplasmic and nuclear inclusions in synucleinopathies, polyglutamine diseases and intranuclear inclusion body disease

Abstract: Ubiquilin-1 (UBQLN1), a member of the ubiquitin-like protein family (UBQLN1-4), is associated with neurofibrillary tangles in Alzheimer's disease (AD) and with Lewy bodies (LBs) in Parkinson's disease (PD) [7]. Mutations in UBQLN2 cause dominant X-linked amyotrophic lateral sclerosis (ALS) [4]. UBQLN2-immunoreactive neuronal cytoplasmic inclusions (NCIs) are found in the hippocampus and spinal cord in ALS with or without UBQLN2 mutation. Moreover, a distinct pattern of UBQLN2 pathology is seen in cases of ALS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
58
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 12 publications
8
58
0
Order By: Relevance
“…Autophagy-mediated selective recycling of the terminally misfolded proteins/aggregates serves as a key component of protein quality control and defects in this pathway have been linked to protein conformation diseases, such as bone, liver, heart and neurodegenerative diseases. 3,[19][20][21][22][23][24][25][26] Misfolded and ubiquitinated proteins are commonly detected in CVB3-infected cells and tissues, suggesting that dysfunction of the protein degradation pathway may have a role in viral pathogenesis. 7,9 We have previously demonstrated that autophagy adapter protein SQSTM1 is cleaved following CVB3 infection, resulting in the loss-of-function of SQSTM1 in selective autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy-mediated selective recycling of the terminally misfolded proteins/aggregates serves as a key component of protein quality control and defects in this pathway have been linked to protein conformation diseases, such as bone, liver, heart and neurodegenerative diseases. 3,[19][20][21][22][23][24][25][26] Misfolded and ubiquitinated proteins are commonly detected in CVB3-infected cells and tissues, suggesting that dysfunction of the protein degradation pathway may have a role in viral pathogenesis. 7,9 We have previously demonstrated that autophagy adapter protein SQSTM1 is cleaved following CVB3 infection, resulting in the loss-of-function of SQSTM1 in selective autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Longer polyglutamine tracts increase the propensity of mutant Htt protein to aggregate, forming ubiquitin-positive inclusion bodies that are a pathological hallmark of HD (Finkbeiner, 2011). Several reports indicate that Htt inclusions contain ubiquilin, a protein that functions in protein clearance through the proteasome and autophagy pathways (Doi et al, 2004; Mori et al, 2012; Rutherford et al, 2013). Interestingly, in R6/2 mice, which recapitulate many features of HD, ubiquilin proteins are not only present in Htt inclusions, but their levels decline progressively during disease progression (Safren et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, even in 100-week-old SCA3 KI mice, when intranuclear and extranuclear inclusion pathology in the brain is maximally robust, UBQLN2 did not colocalize to nuclear inclusions in the CA1 region (Fig.3C) or to extranuclear inclusions in the striatum radiatum (Fig.3D). UBQLN1, closely related to UBQLN2, has been reported to localize to SCA3 nuclear inclusions (Mori et al, 2012). However, immunostaining with an anti-UBQLN antibody that recognizes both UBQLN1 and UBQLN2 (Fig.S1) in 50 and 100-week-old SCA3-KI mice showed neither UBQLN1 nor UBQLN2 colocalization to SCA3 nuclear inclusions (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mutations in this protein directly cause hereditary neurodegenerative disease along the amyotrophic lateral sclerosis (ALS)/frontotemporal dementia (FTD) spectrum (Deng et al, 2011; Zhang and Saunders, 2009). Furthermore, studies of human brain tissue indicate that UBQLN1 and/or UBQLN2 localize to many different types of inclusions including neurofibrillary tangles in AD, Lewy bodies in Parkinson disease, and neuronal nuclear inclusions in polyQ diseases (Mori et al, 2012). There are, however, inconsistencies among published reports regarding the aggregate pathologies sequestering UBQLNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation